DOI: 10.32469/10355/10934
|View full text |Cite
|
Sign up to set email alerts
|

Culturally conditioned privacy in online photosharing: a comparison between American and Chinese users of social network sites

Abstract: This research examines how American Facebook users and Chinese Renren.com users deal with their privacy in photo sharing on social network sites. It has been a long-debated problem whether privacy is culturally specific. This research explores the problem in the context of online communication. Most relating previous studies are quantitative studies that lack in-depth description. This research seeks to provide a rich description and explanation of online privacy in reference to cultures. It recruited 10 Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With the persistence, replicability, scalability, and searchability of online information (as pointed out by boyd, 2010a, cited by Martos, 2013, p. 3), users cannot be assured that what they deemed private will really stay private. In fact, Gurses & Berendt (2001, p. 2) cite about an empirical analyses (which supports the view that "SNS play an active role in the general privacy nightmare of the Internet"), which has shown that "vast amounts of data are collected, often without a clearly defined purpose, that privacy settings are cumbersome and their use poorly communicated, and that privacy setting defaults reveal a lot of information…" Gandy, 2007; Turow, Feldman, & Meltzer, 2005 (cited by Liu & Fan, 2015, p. 2142) also note that as a large part of "social life is conducted online, individual control of personal information often loses out to database marketing or government surveillance." Where does this leave us then?…”
Section: Respondents' Disclosure Based On Their Profilesmentioning
confidence: 97%
See 1 more Smart Citation
“…With the persistence, replicability, scalability, and searchability of online information (as pointed out by boyd, 2010a, cited by Martos, 2013, p. 3), users cannot be assured that what they deemed private will really stay private. In fact, Gurses & Berendt (2001, p. 2) cite about an empirical analyses (which supports the view that "SNS play an active role in the general privacy nightmare of the Internet"), which has shown that "vast amounts of data are collected, often without a clearly defined purpose, that privacy settings are cumbersome and their use poorly communicated, and that privacy setting defaults reveal a lot of information…" Gandy, 2007; Turow, Feldman, & Meltzer, 2005 (cited by Liu & Fan, 2015, p. 2142) also note that as a large part of "social life is conducted online, individual control of personal information often loses out to database marketing or government surveillance." Where does this leave us then?…”
Section: Respondents' Disclosure Based On Their Profilesmentioning
confidence: 97%
“…Sci. 2(4) 23-36, 2023 communicated as noted by Gurses & Berendt, 2001, p. 2; and that such settings "often appear ambiguous to users" as stated by Livingstone, 2008, cited by Liu & Fan, 2015, p. 2143) is likewise being raised in this complex discourse on privacy, the author believes that the more serious matter that merits important attention from users is the fact that marketing industries and the government (the U.S, government, in particular) have access to SNS users' accounts.…”
Section: Respondents' Disclosure Based On Their Profilesmentioning
confidence: 99%
“…When posting profile photos on Facebook, East Asian users were more likely to post fewer photos with their faces than American users (Huang & Park, 2013). When Chinese users shared photos with their families on SNS, they were more likely to block out family members from the photos, post only photos containing imperceptible family members' images, or apply some restrictive settings to allow only a few close friends to see those family photos (Liu, 2010). They were less likely to share photos depicting the images of immediate family members or girl/boyfriends than Americans users.…”
Section: Cultural Differences In Self-expressionmentioning
confidence: 99%